The effect of alpha lipoic acid on the developmental competence of mouse isolated preantral follicles - Talebi, Ali (Springer US, 2012)
PURPOSE: This study was designed to investigate the effect of alpha-lipoic acid (ALA) on reactive oxygen species (ROS) production, total antioxidant capacity (TAC) and developmental competence of cultured pre-antral follicles derived from mouse ovarian tissue. METHODS: Pre-antral follicles were isolated from immature mouse ovaries and were cultured in α- minimal essential medium supplemented with different concentrations (0, 50, 100, 250 and 500 uM) of ALA. Follicular growth, oocyte maturation and embryo development were evaluated. Separately, ROS and TAC were measured after 0, 24, 48, 72 and 96 h of culture with spectrofluorometery and ferric reducing/antioxidant power (FRAP) assay, respectively. RESULTS: In the presence of 100 uM ALA, developmental rates of follicles, oocytes and embryos were significantly higher than other groups (p < 0.05). At 96 h after culture, a decrease in ROS and an increase in TAC were observed in ALA group compared to control group (p < 0.05). CONCLUSION: ALA (100 uM) improves the in vitro development of follicles. This effect may be mediated by decreasing ROS concentration and increasing follicular TAC level during the culture period.‎‎‎